KEBIJAKAN ARAB SAUDI MEMUTUSKAN HUBUNGAN DIPLOMATIK DENGAN QATAR TAHUN 2017 - Nurhafiza "; M. Saeri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
5 June 2017 Saudi Arabia announced severed diplomatic relations with Qatar. Arab Saudi also announced a full blockade of Qatar, closed the land border, seaports and airspace with Qatar. All planes traveling to and from Qatar prevented from landing in Saudi Arabia. Qatar’s diplomats were given 48 hours to leave Saudi Arabia while other Qatari nationals were allowed two weeks to leave. Then Saudi Arabia stopping military ties with Qatar on the Yemeni conflict and closed Al Jazeera news agency in the country. The purpose of this research is to find out what is the reason Saudi Arabia severing diplomatic relations with Qatar in 2017. This research theoretically has built with Realism perspectives on International Relations and supported by Non Traditional Security theory Barry Buzan. Formulation of all arguments, facts, and theoretical framework on this research is guided by qualitative explanation methods. Technique in this research is through by library research. Data which is gotten and collected from books, journals, the last thesis and then from internet as related to the problems. The result of this research found that the reason Saudi Arabia severed diplomatic relations with Qatar for several reasons. First, the potential superiority of Qatar towards Saudi Arabia, especially in the economic field which could threaten Saudi Arabian influence in the gulf region. Second, because the Al Jazeera media owned by Qatar continues announced about the Muslim Brotherhood and and other militant groups that have been designated as terrorist groups by Saudi Arabia. Al Jazeera also became a media that helped spread democracy in gulf region especially when Arab Spring. Last because Qatar and Iran affiliations have made Saudi Arabia feel that Qatar is obedient because it has cooperated with a country that is always considered an enemy by Saudi Arabia.Keywords: Severing Diplomatic Relations, Non Traditional Security, Realism